(3GdMceI GdYQTjIs - (3GdbhGei, GdTjQGRj, UOQ GdOjf, eMeO Hf EHQGgje Hf jMji, J (B1050(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYdfG eef TQM UOQg ddESdGe agh Ydi fhQ ef QHg (B...(3gPg QSGdI CPcQ ajgG WGFaI ef GdeSGFd GdQHhHjI hGdeYGde GdbOSjI(B...s
(3BNQgG (B:s
...(3CYGPfG Gddg hENhGffG GdeDefjf ef TQ GdTjGWjf hGdeVdjf, hfhQ bdhHfG HCfhGQ GdMceI hGdjbjf HeMeO hBdg GdWGgQjf JeJ GdQSGdI GdTQjaI GdehSheI HGdMceI GdYQTjI(B...s
(3JHUQI GdeDda (B:s
(3CQN UGMH GdCYdGe dhaGJg SfI(B: 1059(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B31s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs